SPECIALIZED MODEL OF THE ASSIGNMENT PROBLEM FOR THE SCHEDULE OF ACTIVITIES OF HIGHER EDUCATION INSTITUTIONS - Razumov, S. Yu. (Science and Transport Progress, 2009)
The method for modeling the creation of high school’s schedule as an assignment task with inhomogeneous parameters, and the basic directions of development are considered.